Antimicrobial activity euphorbia hirta plant extracts against escherichia coli and candida albicans / Noramiera Shahrir - Shahrir, Noramiera (Faculty of Applied Sciences, 2017)
Euphorbia hirta is a very popular herb amongst practitioners of traditional herb medicine, widely used as a decoction or infusion to treat various ailments including intestinal parasites, diarrhoea, vomiting, asthma, bronchitis, coughs and venereal diseases. The purpose of this study to find the chemical compounds in E. hirta plant and also to perform antimicrobial study in order to determine the efficiency of E. hirta plants. The powdered plant material was extracted using two solvents methanol and hexane through sequential extraction. Agar well diffusion method was used to determine the antimicrobial activity against Escherichia coli and Candida albicans. The methanol produced the higher yield of. extract than hexane. Phytochemical screening of the crude extracts revealed the presence of alkaloid, flavonoid, terpenoids, tannins, phenolics and glycosides. Presense of bioactive constituents have been linked to the antimicrobial activity of the plant material. Methanol E. hirta extract is more effective in antibacterial than hexane extract. Different concentrations of crude extract show significant difference (P ≤ 0.05). E. hirta plants extract do not show any antifungal activity. The results presented in this study confirmed that extracts of E. hirta hold antibacterial potential effects against pathogenic microorganisms and therefore can be used as a safe, reliable and economical natural antibacterial source for therapeutic treatment.